2020
DOI: 10.1177/1120700020926652
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of total hip arthroplasty using dual-mobility cups for femoral neck fractures: a systematic review and meta-analysis

Abstract: Objectives: Femoral neck fractures (FNFs), with up to 15% mortality, are prominent orthopaedic emergencies. After treating FNFs, dislocation is another challenge increasing morbidity, mortality and treatment costs substantially. The emerging dual-mobility cup (DMC) may decrease dislocation rates following total hip arthroplasty (THA) for FNFs. We performed a systematic review of literature reporting dislocation and mortality rates with DMC-THA for the treatment of FNFs. Methods: 2 authors independently searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 87 publications
(121 reference statements)
1
11
0
3
Order By: Relevance
“…Zagorov et al [34] in 2018 compared postoperative dislocation rate with Dual mobility cup with that of conventional THR and Bipolar Hemiarthroplasty for displaced femoral neck fractures and concluded that DMTHR had 0% dislocation rate as compared to 11.1% in conventional THR and 3.1% in bipolar hemiarthroplasty. Similar comparative studies in the literature [10,11,[27][28][29][30][31] have shown the superiority of DMTHR over conventional THR in terms of postoperative stability and requirement of revision arthroplasty and are enlisted in Table 3. In the present study, no difference was found between postoperative dislocation rate, postoperative stability, implant loosening, and rate of revision surgery between the two groups, as none of the patients had any such complication.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Zagorov et al [34] in 2018 compared postoperative dislocation rate with Dual mobility cup with that of conventional THR and Bipolar Hemiarthroplasty for displaced femoral neck fractures and concluded that DMTHR had 0% dislocation rate as compared to 11.1% in conventional THR and 3.1% in bipolar hemiarthroplasty. Similar comparative studies in the literature [10,11,[27][28][29][30][31] have shown the superiority of DMTHR over conventional THR in terms of postoperative stability and requirement of revision arthroplasty and are enlisted in Table 3. In the present study, no difference was found between postoperative dislocation rate, postoperative stability, implant loosening, and rate of revision surgery between the two groups, as none of the patients had any such complication.…”
Section: Discussionmentioning
confidence: 81%
“…There is some evidence [31][32][33] in line with this finding. On the other hand, systematic review and metanalysis by Canton et al [27] and most of the literature on DMTHR [10,11,28,29,31,34] have either not been compared or have documented functional outcome equivalent to that with the conventional THR. The score was specifically better in activities sections like sitting crosslegged and squatting and in the motion section.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Orthopédie (SOFJO), was the president of SOFCOT in 2016, and he has also been appointed as the chairman for the 39th world congress of la Société Internationale de Chirurgie Orthopédique et de Traumatologie (SICOT) in Montreal.SOFJO introduces a large number of those aiming to study abroad to training facilities. Until March 2017, a total of 82 Japanese and 19 French trainees had studied in France and Japan23) , respectively. If you wish to study abroad, please access the SOFJO website.…”
mentioning
confidence: 99%